Alternative splicing modulates Disabled-1 (Dab1) function in the developing chick retina - Katyal, Sachin (Nature Publishing Group, 2004)
The Reelin–Disabled 1 (Dab1)-signaling pathway plays a critical role in neuronal cell positioning in the brain. We have isolated two alternatively spliced variants of Dab1 from chick retina, an early form (chDab1-E) expressed in undifferentiated cells and a late form (chDab1-L) expressed in amacrine and ganglion cells. A key difference between the two forms is the exclusion in chDab1-E of two Src-related tyrosine kinase recognition sites implicated in Reelin-mediated Dab1 tyrosine phosphorylation. Retinal cultures transfected with a chDab1-L expression construct undergo a dramatic change in morphology, accompanied by the formation of numerous thin elongated processes, increased tyrosine phosphorylation, activation of Src family kinase(s) and increased levels of the axonal outgrowth protein growth-associated protein-43. In contrast, chDab1-E transfectants retain an undifferentiated morphology. Mutational analysis implicates a specific tyrosine (tyr-198) in the morphological and biochemical alterations associated with chDab1-L expression. We propose that alternative splicing of chDab1 represents an effective and flexible way of regulating the Reelin–Dab1-signaling pathway in a mixed cell population, by ensuring that secreted Reelin activates the signaling cascade only in target neuronal cells.